Nikah Misyar: Aspek Maslahah Dan Mafsadah - Zainuri Chamdani (Fakultas Hukum, Universitas Islam Bandung, 2021)
Marriage is one of the sunnah and things chosen by Allah, to reproduce offspring, and to continue human life. So that the practice of marriage has various purposes, namely to maintain offspring, to continue and maintain the safety of life between humans, because it is a form of ta'abbudiyah (servitude) and obedience to every command. This paper aims to examine what is meant by Nikah Misyar and how the law and Maslahah and Mafsadah are. This research is in the form of literature review where the legal source comes from documents or books in accordance with the theme of this research. The data that has been collected is analyzed in the context of mu'tabarah fiqh, so that it gets good and comprehensive analysis results. The scientific study of Misyar Nikah should further spread the explanation of Maslahah and Mafsadah especially to the common people, especially in Indonesia.